2021
DOI: 10.1177/23259582211052399
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Care for People With HIV in Tanzania: Provider Perspectives and Opportunities for Improvement

Abstract: One in three people with HIV (PWH) has hypertension. However, most hypertensive PWH in sub-Saharan Africa are unaware of their hypertension diagnosis and are not on treatment. To better understand barriers to hypertension care faced by PWH, we interviewed 15 medical providers who care for patients with HIV and hypertension in northern Tanzania. The data revealed barriers at the patient, provider, and system level and included: stress, depression, and HIV-related stigma; lack of hypertension knowledge; insuffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Participants reported low awareness of the risk factors, signs and management of hypertension similar to other studies conducted in the region2–4 18 despite large public awareness on HIV. The existing HIV infrastructure can support increased public education for hypertension and other non-communicable diseases (NCDs) at the patient, family, community and healthcare system levels, for example, through interpersonal communication between the patient and provider, community screening engagements, mass media campaigns and training of healthcare providers on screening 16.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Participants reported low awareness of the risk factors, signs and management of hypertension similar to other studies conducted in the region2–4 18 despite large public awareness on HIV. The existing HIV infrastructure can support increased public education for hypertension and other non-communicable diseases (NCDs) at the patient, family, community and healthcare system levels, for example, through interpersonal communication between the patient and provider, community screening engagements, mass media campaigns and training of healthcare providers on screening 16.…”
Section: Discussionsupporting
confidence: 65%
“…Similar to a Tanzania study evaluating hypertension care for PLWH, providers noted system-related capacity limitations (staff, medications) and high costs of treatment as the underlying individual-level barriers and recommended prioritisation of resources and funding towards hypertension care. 18 Ongoing NHIF reforms to expand care for NCDs signal hope to patients, 22 and as policy makers consider integrated NCD management within and outside the existing HIV infrastructure, subsidies towards clinician consultation, diagnostics and medication will go a long way in improving the care cascade.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Tanzania showed barriers in integrating hypertension management for HIV control. The barriers were lack of hypertension knowledge, inefficient prescriptions, a lack of communication on related issues and hypertension care, in addition to high prices for healthcare in general, a lack of routine hypertension screening and follow-up 50 . In our study, almost 47.25% of HIV patients with hypertension were undiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Further study is needed to explore reasons for low uptake of these medications, since all participants were referred to an adjacent general practitioner if they were found to have elevated blood pressure or hyperglycemia at initial enrolment. Recent qualitative studies have identified multiple barriers to anti-hypertensive and anti-hyperglycemic therapies among PWH in Tanzania, including fear, lack of understanding, and cost [ 30 , 31 ]. In contrast to antiretroviral therapies, anti-hypertensive and anti-hyperglycemic medications are not provided free-of-charge in Tanzania.…”
Section: Discussionmentioning
confidence: 99%